Performance evaluation of demountable shear connectors with collar step at ambient and elevated temperatures. (1st September 2019) - Sencu, R.M.; Wang, Y.C.; Yang, J.; Lam, D.
Highlights: The work presented is in line with the new circular economy concepts for enabling steel-concrete composite structures to deconstruct. The paper addresses for the first time the behaviour of demountable shear connectors at elevated temperature conducted at the University of Manchester over a period of over 2 years' time. The results are important for both the standard committees and modelling practitioners, especially for providing the results of advanced testing programmes. Abstract: This paper presents the results of an experimental programme to investigate the performance of a new composite shear connector that can be used to build deconstructable composite floors. A total of 21 push-out tests were conducted to quantify the effects of different design parameters, including different nominal temperature levels ( 20 °C, 100 °C, 300 °C, 450 °C, 600 °C), with the steel decking perpendicular and parallel to the steel section, two different embedded shear stud lengths and two different grades of concrete ( C40/50 and C20/25). The tests were mainly carried out under steady-state condition where the specimen temperatures were increased to the desired target and the load was then applied until failure of the specimen. A few transient tests were also carried out, in which a load equal to the load carrying capacity of the steady-state test at 600 °C was applied, followed by increasing the specimen temperature until failure. Three modes were observed: ( i ) concrete crushing with stud fracture, ( ii ) stud fracture and ( iii ) concrete pull-out. Concrete pull-out occurred only on one specimen with concrete grade C20/25 . It is found that the main failure mode at elevated temperatures not exceeding 400 °C was initiated by concrete crushing, concomitantly producing ductile stud damages. At elevated temperatures above 400 °C, the failure mode changed to shear stud fracture. The Eurocode 4 calculation equations were shown to produce shear connector resistances to be in reasonable agreement with the steady state results for the higher-grade concrete, even though the previous equations were developed for welded shear studs. The transient state tests failed at lower temperatures than the target temperature of 600 °C, indicating it may not be safe to use steady state tests for evaluation of shear connector resistance at high temperatures.